Integrating business management processes. Volume 2, Support and assurance processes - De Silva, Titus (New York, NY : Routledge, 2021)
Integrating Business Management Processes: Volume 2: Support and Assurance Processes (978-0-367-48548-1) Shelving Guide: Business & Management The backbone of any organisation is its management system. It must reflect the needs of the organisation and the requirements of its customers. Compliance with legal requirements and ethical environmental practices contributes towards the sustainability of the management system. Whatever the state of maturity of the management, this book, one of three, provides useful guidance to design, implement, maintain and improve its effectiveness. This volume provides a comprehensive coverage of the key support and assurance processes. Topics include document control, communication, marketing, information systems and technology, human resource management, training and development, customer relations management, financial management and measurement and analysis to name a few. This book, with its series of examples and procedures, shows how organisations can benefit from satisfying customer requirement and the requirements of ISO standards to gain entry into lucrative markets. Titus De Silva is a consultant in management skills development, pharmacy practice, quality management and food safety and an advisor to the newly established National Medicines Regulatory Authority (NMRA) in Sri Lanka.
2.8 Barriers to Effective Communication -- 2.8.1 Organisational Barriers -- 2.8.2 Cultural Barriers -- 2.8.3 Physical Barriers -- 2.8.4 Semantic Barriers -- 2.8.5 Socio-Psychological Barriers -- 2.9 How to Overcome Communication Barriers -- 2.10 How to Improve the Effectiveness of Conversations -- 2.11 Communication Skills -- 2.12 Manager's Role in Communication -- 2.13 Communicating Quality, Environmental and Food Safety Issues -- 2.13.1 Internal Communication -- 2.13.1.1 Quality Issues -- 2.13.1.2 Environmental Issues -- 2.13.1.3 Food Safety Issues -- 2.13.2 External Communication -- 2.13.2.1 Quality Issues.
"A Productivity Press book."
OCLC-licensed vendor bibliographic record.
Keywords: Industrial management; Environmental management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management